Relational pedagogical mediation and technological automation in higher education: a scoping review from the TRIC paradigm - Villegas Velasco, Rafael; López Pérez, Myriam (Sekkan Revista de Ciencias Sociales y Humanidades, 2026)
The digitalization of higher education, intensified by the global health crisis and the integration of Generative Artificial Intelligence (GAI), has configured learning environments primarily oriented toward operational efficiency, with documented implications for the relational dimension of the educational process. This article examines the role of the Relational Factor (R Factor) within the TRIC paradigm (Technologies of Relationship, Information and Communication) as a conceptual framework for understanding and reorienting teaching practices in digital higher education contexts. A scoping review was conducted following the Arksey and O’Malley (2005) protocol, based on a systematic search in Scopus, EBSCOhost, Web of Science, Redalyc, and SciELO, limited to the period 2016-2026. The final analytical corpus consisted of 45 sources selected according to explicit criteria of conceptual relevance and academic quality. The findings identify three main mechanisms through which technological automation erodes the pedagogical bond: the depersonalization of feedback, the temporal compression of reflection, and the normalization of student isolation. Building on this diagnosis, the article proposes relational pedagogical mediation, articulated across diagnostic, design, and ethical dimensions, as both an analytical category and a professional practice for teaching in technology-mediated environments. The need for empirical research in Latin American contexts examining the impact of these practices on variables such as academic persistence and institutional belonging is also identified. The study concludes that technological integration in higher education requires incorporating the relational dimension as a central criterion in pedagogical design, teacher training, and educational quality assessment.